1995
DOI: 10.1111/j.1747-6593.1995.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Leakage through Synthetic Landfill Liner Materials

Abstract: The introduction of synthetic lining materials for leachate containment and the prevention of groundwater contamination was an important development in landfill technology. These materials have a low hydraulic conductivity which results in minimal leachate release by bulk fluid flow (advection) provided that the barrier (and its construction) is free from defects. However, the effectiveness of these materials as barriers cannot be confirmed unless contaminant release by diffusion is also taken into considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Behaviour of inorganic contaminants Introduction Current landfill liner systems are designed primarily as low permeability structures and commonly incorporate compacted clays or other mineral layers with synthetic membranes in composite or multi-barrier arrangements (Murray et al 1992;Seymour 1992). punctures and tears) often introduced during waste emplacement may reduce the effectiveness of the synthetic membrane (Buss et al 1995). This permeability specification may be difficult to obtain and test in the mineral layer under field conditions (Pierce et al 1986;Daniel & Brown 1988).…”
mentioning
confidence: 99%
“…Behaviour of inorganic contaminants Introduction Current landfill liner systems are designed primarily as low permeability structures and commonly incorporate compacted clays or other mineral layers with synthetic membranes in composite or multi-barrier arrangements (Murray et al 1992;Seymour 1992). punctures and tears) often introduced during waste emplacement may reduce the effectiveness of the synthetic membrane (Buss et al 1995). This permeability specification may be difficult to obtain and test in the mineral layer under field conditions (Pierce et al 1986;Daniel & Brown 1988).…”
mentioning
confidence: 99%
“…sand, soil and air) [14,[17][18][19]. This was used to evaluate the rate of solvent and contaminant transport across the tubular polymer membrane from inside to outside.…”
Section: Permeation Testsmentioning
confidence: 99%
“…Figure 1 shows the schematic profile of a typical single-liner system which consists of a leachate collection layer (k~10 −1 m/s), a compacted clay layer (k~10 −9 m/s) covered with high-density polyethylene (HDPE) geomembrane (GMB) and a leak detection/recovery layer (k~10 −1 m/s), where k is the hydraulic conductivity (Shukla and Yin, 2006). While the liners are expected to be intact over their operating lifespan, due to various factors such as poor placement assurance, insufficient quality control and harsh conditions of operation, it is observed that the integrity of these liners is often compromised (Buss et al, 1995;Giroud, 1984;Giroud and Bonaparte, 1989;Hoyos et al, 2015). Defects frequently develop in liners, resulting in leachate leakages and consequent contamination issues (Ben Othmen and Bouassida, 2013).…”
Section: Introductionmentioning
confidence: 99%